1982
DOI: 10.1111/j.1559-1816.1982.tb00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Weapons and Eye Contact as Instigators or Inhibitors of Aggressive Arousal in Police‐Citizen Interaction1

Abstract: A field experiment was conducted with police officers during the normal course of their traffic patrol duties. The purpose was to determine whether the presence of holstered weapons and mirror sunglasses affected the degree of aggressiveness expressed nonverbally, and reported on a mood scale by citizens halted for an information check (neutral condition) or in order to be given a traffic ticket (negative condition). Results indicated that subjects in the negative condition both expressed and reported more agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…The notion that incidentally present negative or aggression cues generally enhance aggressiveness among individuals already experiencing negative affect was strongly supported. Both the median and mean effect size (.50 and .38, respectively) fell within the range of what Cohen (1977) de- " Loew, 1967" c Turner & Simons, 1974" Turner & Simons, 1974 Turner & Simons, 1974 Turner & Simons, 1974 Turner & Simons, 1974 Turner & Simons, 1974Boyanowski & Griffiths, 1982 scribed as a medium degree of effect. The aggression-enhancing tendency of cues is highly reliable (p < .0001), and the resulting fail-safe n of 628 is clearly large enough to rule out publication bias as an explanation of the overall result.…”
Section: Methodsmentioning
confidence: 68%
“…The notion that incidentally present negative or aggression cues generally enhance aggressiveness among individuals already experiencing negative affect was strongly supported. Both the median and mean effect size (.50 and .38, respectively) fell within the range of what Cohen (1977) de- " Loew, 1967" c Turner & Simons, 1974" Turner & Simons, 1974 Turner & Simons, 1974 Turner & Simons, 1974 Turner & Simons, 1974 Turner & Simons, 1974Boyanowski & Griffiths, 1982 scribed as a medium degree of effect. The aggression-enhancing tendency of cues is highly reliable (p < .0001), and the resulting fail-safe n of 628 is clearly large enough to rule out publication bias as an explanation of the overall result.…”
Section: Methodsmentioning
confidence: 68%
“…Moreover, those who associate with people having such interests should also be mindful of the implications of this research. It has rn!en shown that people who are merely in the presence of weapons exhibit increased aggression (e.g., Berkowitz, 1981;Berkowitz & LePage, 1967;Boyanowsky & Griffiths, 1982;C.W Turner, Simons, Berkowitz, & Frodi, 1977). The original experiment on the topic (Berkowitz & LePage, 1967) provided subjects with the opportunity to aggress (shock) against an experimental confederate in a setting in which a gun had been "carelessly" left lying nearby.…”
Section: Situational Determinantsmentioning
confidence: 99%
“…possession of a weapon). Boyanowsky and GriYths (1982) con rmed that the presence of visible holstered weapons resulted in more aggressive behaviour than when the weapon was not visible. The issue of whether guns may be carried 'concealed' or 'unconcealed' (controversial in some American states) has no real equivalent as yet in the UK.…”
mentioning
confidence: 87%